2001
DOI: 10.1161/01.cir.103.7.926
|View full text |Cite
|
Sign up to set email alerts
|

Pravastatin Treatment Increases Collagen Content and Decreases Lipid Content, Inflammation, Metalloproteinases, and Cell Death in Human Carotid Plaques

Abstract: Background-The clinical benefits of lipid lowering with statins are attributed to changes in plaque composition leading to lesion stability, but supporting clinical data from human studies are lacking. Therefore, we investigated the effect of 3 months of pravastatin treatment on composition of human carotid plaques removed during carotid endarterectomy. Methods and Results-Consecutive patients with symptomatic carotid artery stenosis received 40 mg/d pravastatin (nϭ11) or no lipid-lowering therapy (nϭ13; contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

44
534
9
22

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 925 publications
(614 citation statements)
references
References 51 publications
44
534
9
22
Order By: Relevance
“…After this early phase, the increase in PWV tends to disappear and is even reversed as a consequence of the remodelling of the vascular wall. [10][11][12]28 Such experimental findings agree with the slight increase in PWV that we observed in the present study after the 12-week treatment.…”
Section: Commentssupporting
confidence: 93%
See 2 more Smart Citations
“…After this early phase, the increase in PWV tends to disappear and is even reversed as a consequence of the remodelling of the vascular wall. [10][11][12]28 Such experimental findings agree with the slight increase in PWV that we observed in the present study after the 12-week treatment.…”
Section: Commentssupporting
confidence: 93%
“…[8][9][10][11][12]28 Furthermore, in patients with hypercholesterolaemia, radial artery compliance was found to increase to a larger extent after a two-year treatment than after a six-month treatment of simvastatin. 15,29 Finally, all these findings taken together agree with the clinical observations that, although favourable changes in lesion composition were observed within three months of statin treatment, clinical trials suggest that event reduction takes six-twelve months after initiation of treatment.…”
Section: Commentsmentioning
confidence: 91%
See 1 more Smart Citation
“…Whereas candesartan was effective at reducing inflammation as evidenced by a decrease in macrophage infiltration and MCP-1 levels in the plaque, rosuvastatin did not have such a marked effect on these parameters. Previous studies have shown reduced inflammation in plaques from people with and without type 2 diabetes in response to various statins [17,43].…”
Section: Discussionmentioning
confidence: 95%
“…While a reduction in LDL-cholesterol was observed in many of these studies, it is now considered that statins also mediate pleiotropic antiatherogenic effects that are independent of their effects on lipoproteins, and that this action may contribute to their efficacy in reducing cardiovascular events. Indeed, HMGCoA reductase inhibitors have been shown to attenuate, although not in the context of diabetes, many of the stages critical to atherosclerotic plaque development including monocyte chemotaxis [13], neutrophil-endothelial cell interaction [13], smooth muscle cell apoptosis [14], migration [15] and proliferation [16], as well as plaque stability [17].…”
Section: Introductionmentioning
confidence: 99%